Pengaruh Model Inkuiri Berbasis Etnobotani Terhadap Kemampuan Literasi Tumbuhan dan Kesadaran Berkelanjutan Siswa SMAN 1 Suliki pada Materi Sistem Pencernaan - Fifi Refita Wati; Fitri Arsih (Al-Alam: Islamic Science Education Journal, 2026)
This study aimed to determine the effect of an ethnobotany-based inquiry model on the plant literacy skills and sustainability awareness of students at SMAN 1 Suliki regarding the digestive system topic. A quasi-experimental method with a pretest-posttest control group design was employed. The sample was selected using purposive sampling: class XI F5 served as the experimental group (receiving the ethnobotany-based inquiry model), while class XI F3 served as the control group (receiving the direct instruction model). Data were collected through tests and questionnaires assessing plant literacy skills and sustainability awareness. The results showed that the experimental group achieved a higher N-Gain in plant literacy skills compared to the control group (which fell into the low category). Regarding sustainability awareness, the experimental group achieved an N-Gain in the medium category across all indicators (0.57–0.61), also outperforming the control group. Hypothesis testing yielded a significance value of 0.000 (< 0.05) for all indicators across both variables. Thus, it can be concluded that the ethnobotany-based inquiry model has a positive and significant effect on the plant literacy skills and sustainability awareness of SMAN 1 Suliki students regarding the digestive system topic.